Eight new species of the spider genus Khorata Huber, 2005 (Araneae: Pholcidae) from China - Yao, Zhiyuan; Nie, Lei; Li, Shuqiang (Zootaxa, 2019)
Eight new species of the genus Khorata Huber, 2005 are reported from China: Khorata dawei Yao & Li sp. nov. (Yunnan), K. libo Yao & Li sp. nov. (Guizhou), K. luoping Yao & Li sp. nov. (Yunnan), K. matang Yao & Li sp. nov. (Yunnan), K. qian Yao & Li sp. nov. (Guizhou), K. suwei Yao & Li sp. nov. (Guangxi), K. wenshan Yao & Li sp. nov. (Yunnan), K. yangchun Yao & Li sp. nov. (Guangdong). All new species are described from males and females. Type material is deposited in the Institute of Zoology, Chinese Academy of Sciences (IZCAS) in Beijing, China.